2017
DOI: 10.1515/jtim-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D levels in treatment-naïve chronic hepatitis B patients

Abstract: Background and Objectives: According to the demographic health survey conducted in 2015, Egypt had 10% documented prevalence of anti-HBc positive patients aged 1-59 and 1% viremic patients amongst the population in the same age group, with a domination of genotype D. Several studies claimed the possible role of vitamin D deficiency in hepatitis B virus (HBV) replication and disease progression. Patients and Methods: Serum vitamin D levels [25(OH) D3] were assessed in 96 HBeAg negative non-cirrhotic chronic HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some studies have been carried out in patients with some chronic viral infections, like HBV, HCV, and HIV. These trials have shown the following in chronically infected patients: (a) serum concentrations of vitamins A, E, D and C are decreased [72,73], (b) vitamins A, D, E and C deficiency is associated with higher levels of viral replication as well as with higher titers of pro-inflammatory cytokines, like IL-6 and TNF-α, or with illness severity in some studies carried out in different virus-associated diseases [72][73][74][75][76][77][78][79], (c) vitamins may suppress or reduce viral replication or load in different virus infections both in adults and in children [80][81][82][83][84].…”
Section: The Current Knowledge On the Possible Activity Of The Liposomentioning
confidence: 99%
“…Some studies have been carried out in patients with some chronic viral infections, like HBV, HCV, and HIV. These trials have shown the following in chronically infected patients: (a) serum concentrations of vitamins A, E, D and C are decreased [72,73], (b) vitamins A, D, E and C deficiency is associated with higher levels of viral replication as well as with higher titers of pro-inflammatory cytokines, like IL-6 and TNF-α, or with illness severity in some studies carried out in different virus-associated diseases [72][73][74][75][76][77][78][79], (c) vitamins may suppress or reduce viral replication or load in different virus infections both in adults and in children [80][81][82][83][84].…”
Section: The Current Knowledge On the Possible Activity Of The Liposomentioning
confidence: 99%
“…(i) A large series of clinical studies have shown that the serum concentrations of vitamins A, E and D are decreased in patients with some chronic viral infections, like HBV, HCV and HIV (60,61) , in comparison with uninfected individuals as well as in aged patients (62) . (ii) The deficiency of vitamins D, E and A is associated with higher levels of viral replication as well as with higher values of inflammatory cytokines, like IL-6 and TNF-α (63)(64)(65) .…”
Section: Defective and Dysfunctional Immune Response In Patients Withmentioning
confidence: 99%
“…A decreased liver function might be one explanation for the low vitamin D levels seen in chronic liver diseases. Hepatic damages result in lower synthesis of vitamin D carrier proteins such vitamin D binding protein and albumin, as well as reduced vit D hepatic hydroxylation to 25(OH)D3 or calcidiol [ 24 ]. In a review published in 2012, Stokes et al.…”
Section: Introductionmentioning
confidence: 99%